Peranan Media Sosial Instagram @Narinkovilda (AWKARIN) Dalam Pembentukan Gaya Hidup Generasi Z - Ilena Putri Salsabilla; Eka Yonavilbia (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2026)
Social Media is currently in great demand by many Indonesians especially the social media instagram. Social media instagram @Narinkovilda is one of her many users on instagram is followed by millions of teenagers in Indonesia. Lifestyle and the activity shared by social media @Narinkovilda is very influenced and play an active role for teenagers who follow him. But not only does the lifestyle look luxurious, but there are also many positive things which was shared on social media instagram @Narinkovilda. Therefore, the purpose of this study is to determine what role is in social media instagram @Narinkovilda as a lifestyle formation Generation Z. The research method used is descriptive qualitative with the theory of uses and effects using data collection techniques documentation and observations on Instagram @Narinkovilda and interviews conducted with informants. Results of this study indicate that the Instagram social media account @Narinkovilda has role in the formation of the lifestyle of Generation Z through positive content and the negative that is in the instagram account.